Gender representation of women’s language in Anne with an E: a study of sociolinguistics - Helmie, Jauhar; Salsabila, lya Ismiati (Nashir Al-Kutub Indonesia, 2024)
Language and gender are inextricably linked and have been the focus of extensive study in sociolinguistics studies. The language features between men and women use are different as women's speech appears to be weaker than men's in many ways. Famous Netflix series entitled Anne with an E provides a unique context for examining women's language features as it is set in the late 19th century and features a young female protagonist who navigates a patriarchal society. The researcher aims to examine the types and factors of women’s language features performed by the female main character in Anne with an E based on Lakoff’s theory. This research uses qualitative method. The primary data source is the utterances extracted from a transcribed first episode of season 1 of the series. The first finding showed that Anne Shirley used 226 women’s language features and all 10 types was found. The most used type was intensifier with 63 (27.87%) data acquired. She used it to emphasize her feelings, thoughts, and experiences, reflecting her expressive and emotive nature. Meanwhile Marilla Cuthbert used 99 women’s language features and 8 from 10 types was found. The most used type was lexical hedge or filler with 34 (34.34%) data acquired. As a responsible adult and caretaker character, she used it to soften assertions or to give herself time to formulate her thoughts. The second finding reveal that both Anne Shirley’s and Marilla Cuthbert’s use of women’s language features were influenced by physiological factors, psychological factors, and social (cultural and historical) factors. The analysis demonstrated that both of their language features in this series are deeply influenced by their backgrounds and characters. The use of women's language features in the series Anne with an E implies that gender differences in language are not only influenced by biological factors but also by psychological, social, and historical factors that shape how individuals communicate in a patriarchal society.